On a unique solution of fractional differential system - Muayyad Mahmood Khalil (Tikrit Journal of Pure Science)
The aim of the study is to investigate the existence and uniqueness of solutions for a semi linear fractional differential system via Banach fixed point theorem. The study proved the existence and uniqueness of solution for a fractional differential system with initial conditions by using contraction mapping theorem, existence and uniqueness results are obtained. Some examples are chosen to illustrate the validity of our results.